Growth performance of Clarias gariepinus juvenile fed diets containing soaked date palm seed meal (Agriculture, Food, and Natural Resources Journal, 2025)
A feeding trial was conducted to investigate the effect of soaked date palm seed meal (Dactylus phoenix) on the growth performance and digestibility of Clarias gariepinus. A total of one hundred and fifty juvenile specimens of catfish (Clarias gariepinus), exhibiting an average weight of 13.94 ± 1.96 (mean ± SD), were allocated to individual plastic bowls (33 liters). Four iso-nitrogenous diets comprising 40% crude protein were formulated, wherein maize was substituted by soaked date palm seed meal at replacement levels of 0% (Diet 1), 25% (Diet 2), 50% (Diet 3), 75% (Diet 4), and 100% (Diet 5). The juveniles were administered a feeding regimen of 5% of their body weight daily over a duration of 42 days. At the conclusion of the experiment, it was determined that the inclusion of Soaked Date Palm Seed Meal (SPSM) was most advantageous as an energy supplement when incorporated at a 50% replacement level. The recorded values for weight gain, specific growth rate (SGR), feed conversion ratio (FCR), and protein production value (PPV) were 35.60 g, 2.25% per day, 2.58, and 0.56, respectively, which were observed to be maximal in the fish receiving Diet 3. The final weights of the fish did not exhibit significant differences (P>0.05) across the various diet groups. Furthermore, there was no statistically significant difference (P>0.05) in FCR among the dietary treatments. Based on these findings, it is recommended that a 50% inclusion of soaked date palm seed in the diet is optimal for juvenile Clarias gariepinus, without compromising growth rates or adversely affecting digestibility parameters.
Keywords: Aquaculture; Catfish; Date palm; Digestion alternative feed; Feed conversion ratio